A EXPANSÃO DOS CURSOS DE SERVIÇO SOCIAL EM TEMPOS DE CONTRAREFORMA DO ENSINO SUPERIOR BRASILEIRO: impactos na formação profissional em Serviço Social - Larissa Dahmer Pereira (Universidade Federal do Maranhão, 2010)
This paper aims to analyze the expansion of courses in Social Work in times of the counter-reform of the Brazilian university education, through a description of the expansion of the courses in Social Work in the post-1990, in the presence and distance modalities. Then it examines the possible impacts of the counter-reform of university education in training in Social Work, problematizing the impact of the ongoing process to quality training and professional profile advocated by the Guidelines Curriculum of the Brazilian Association of Education and Research in Social Work (AERSS).